2018
DOI: 10.1002/hpm.2505
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between exposure to mass media and health insurance enrolment in Ghana

Abstract: Although previous studies have explored the National Health Insurance Scheme (NHIS) in Ghana, very little attention is paid to the influence of mass media exposure on NHIS enrolment. Yet, understanding this linkage is important, particularly due to the critical role of mass media in disseminating health information and shaping people's health perceptions and choices. Using data from the 2014 Ghana Demographic and Health Survey, we employed logistic regression analysis to understand the relationship between NHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Second, traditional gendered roles and notions of masculinity may have worked overtime to make men less responsive to health information and increasingly alienated from health messaging by health professionals and programs. On the other hand, women's reproductive roles have shaped out to make them primary healthcare givers in households, and therefore the target of most health information education sessions 28,40 . These findings are generally consistent with the work of Smidt, 41 who discusses the role of religion as a form of social support that provides opportunities for employment and access to health information to improve members' health and wellbeing.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Second, traditional gendered roles and notions of masculinity may have worked overtime to make men less responsive to health information and increasingly alienated from health messaging by health professionals and programs. On the other hand, women's reproductive roles have shaped out to make them primary healthcare givers in households, and therefore the target of most health information education sessions 28,40 . These findings are generally consistent with the work of Smidt, 41 who discusses the role of religion as a form of social support that provides opportunities for employment and access to health information to improve members' health and wellbeing.…”
Section: Discussionsupporting
confidence: 71%
“…The fact that most health messaging in Ghana is carried out in the official English language, it may be difficult for those with no formal education to independently digest information on HBV transmission without the assistance of health workers. As observed by Gyimah et al, 40 formal education is vital for health information dissemination and exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Turning to access to information, we find that access to information increases the odds of enrolment as well as renewing membership in CBHI. Availability of information has been previously studied before in Ghana 71 and Burkina Faso. 72,73 In Burkina Faso, access to information was studied through an information, education and communication campaign while in Ghana it was studied through listening to radio, television or newspapers.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Third, limited awareness of the new benefits and premiums by the poor, elderly, unemployed, informal sector workers, people in the rural areas and those with disabilities due to varying access to mass media and NHIF service points, a policy implementation issue, led to variations in enrolment, access to care and unnecessary OOP payments. Studies in Nigeria, Burkina Faso, Kenya and Ghana have shown that awareness of insurance schemes affects participation and enrolment [56,[60][61][62] as well as service utilisation among enrolees as seen in India [63]. A guiding principle for purchasers is that communication of UHC-inspired reforms should inform the population of their entitlements and obligations [2,64] through public provision of detailed but simplified information on included and excluded services and the associated levels of OOPs [30,65].…”
Section: Equity Implicationsmentioning
confidence: 99%